Análise de estratégias de comercialização das empresas em tempos de Covid-19 - Menezes, Lara Vitória Targino de (Universidade Federal Rural do Semi-Árido, 2021)
This work aims to analyze the commercialization strategy of companies in times of covid-19. The research was carried out through an online questionnaire “Digital marketing platforms as a strategy in the COVID-19 pandemic” via Google Forms, which aims to identify the need to implement digital platforms as a strategy in the new economic scenario, with a total of 57 correspondents. Data analysis took place through the data collected and imported in the form of graphs, where it is possible to note positivity in the insertion of digital platforms for having great public acceptance and for being the smartest means to be adhered to leverage the economy amidst the pandemic.
Keywords: Covid-19; Plataformas digitais de comercialização; Estratégia; Digital marketing platforms; Strategy; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA